2013
DOI: 10.1177/0143034312472760
|View full text |Cite
|
Sign up to set email alerts
|

Stressful events and depression among Chinese adolescents: The mitigating role of protective factors

Abstract: This study examines the role of salient external factors (family, peer and school caring relations) and internal factors (goals and aspirations, problem solving and self-efficacy, empathy, and self-awareness) in protecting adolescents experiencing interpersonal problems and academic pressure from depression. A total of 1,297 eighth and ninth grade students in Shandong province of Eastern China completed self-report measures. Results of hierarchical regression analyses indicated that interpersonal problems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 25 publications
(29 reference statements)
2
24
1
Order By: Relevance
“…Martin (2013) investigated individual and school factors in his examination of the relationship between academic buoyancy, academic resilience, and negative outcomes in Australian youth. Zhang, Li, Gong, & Ungar (2013) not only considered the influence of individual and school factors, but also the roles of family and peer factors--and their interactions--in protecting at-risk adolescents from depression. Ungar and Liebenberg (2013) also considered the interaction between several ecological levels, examining how cultural and community factors interact with individual factors to predict school participation in multiply risked youth.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Martin (2013) investigated individual and school factors in his examination of the relationship between academic buoyancy, academic resilience, and negative outcomes in Australian youth. Zhang, Li, Gong, & Ungar (2013) not only considered the influence of individual and school factors, but also the roles of family and peer factors--and their interactions--in protecting at-risk adolescents from depression. Ungar and Liebenberg (2013) also considered the interaction between several ecological levels, examining how cultural and community factors interact with individual factors to predict school participation in multiply risked youth.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Therefore, the potential interactions among SLE and the COMT and MAOA polymorphisms may vary across distinct domains of stressful events, however, to our knowledge, this assumption still remains to be studied. The stressors included in the present study are limited to interpersonal problems and academic pressure, because previous research has indicated that in China both of the stressors are two SLEs that adolescents are frequently exposed to Liu et al (1997) and Guo et al (2009) , and furthermore may cause even greater problems for Chinese adolescents ( Zhang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It takes tremendous courage to intervene against bullying. As peer pressure is known to be associated with negative mental health outcomes such as depression [ 13 , 14 ] and social anxiety [ 15 ], it is therefore possible that defending behaviors would also be associated with such mental health outcomes. However, to date no study has explored the relationship between defending behaviors and mental health.…”
Section: Introductionmentioning
confidence: 99%